Study to determine the impact of seatbelt on Maxillofacial bone fractures and associated injuries in road traffic accidents in Saudi Arabia: A 10 years retrospective study - Bayapa Reddy Narapureddy; Shaik Mohammed Asif; Adam Dawria; Nazim Nasir; Faheem Ahmed; Ali Mohieldin; Abdelrhman A. G. Altijani; Hytham Hummad; Awad Osman Abdalla Mohamed; Amna Hamid Imam Babeker; Sunil Kumar Vaddamanu (PLoS ONE, 2025)
Background Every year around the world road traffic accidents (RTAs) cause 1.19 to 1.35 million deaths and 20–50 million non-fatal injuries that result in long-term disabilities and loss of potential life years (YPLL). These injuries have far-reaching consequences that extend beyond the injured person to impact both their families and their wider communities. The Middle East shows a wide range of death rates from RTAs and Saudi Arabia experiences the highest fatality rate. This study aims to identify different maxillofacial fractures and other skeletal fractures in road traffic accident victims while investigating seatbelt usage’s correlation with maxillofacial fractures and also examines demographic variables (age, gender) and crash-related factors (seating position, vehicle type) to contextualize seatbelt efficacy. The study evaluated road traffic accident cases from a retrospective record-based dataset spanning 2011–2021 during the period from January 2023 through May 15th 2023 and marked 542 records with complete details as eligible after filtering. Out of 3629 RTA records, 907 (25%) were randomly selected. Among these, 542 (65%) met the inclusion criteria and were analyzed. The male population comprised 76% of the 412 victims and 82.8% of the victims neglected seatbelt usage while 284 of the 542 participants experienced multiple bone fractures and 126 individuals suffered from single maxillofacial bone fractures. The mandible fracture was the most common facial bone injury with 246 cases (45.3%), followed by Lefort1 fractures which occurred 244 times (45.0%), and Zygomatic maxillary complex fractures which had 216 occurrences (39.8%). Conclusion Research results highlight the necessity for stronger public health strategies and road safety programs to improve seatbelt usage and decrease injury severity in road traffic accidents. Research findings indicate specific vehicle safety design enhancements needed to prevent facial injuries more effectively.